A symbolic computation toolbox for the design of dynamical adaptive nonlinear controllers - Rios-Bolívar, E. Miguel; Zinober, Alan S.I. (Zielona Góra: Uniwersytet Zielonogórski)
We describe a new symbolic computation toolbox BACKDSMC developed using the MATLAB Symbolic Toolbox and intended for the design of dynamical adaptive nonlinear controllers for regulation and tracking tasks of a class of observable minimum phase uncertain nonlinear systems.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka